Design, analysis, and validation of Radio Research Agency reverberation chamber. (24th November 2020) - Yousaf, Jawad; Lee, Hosang; Faisal, Muhammad; Junhee, Han; Nah, Wansoo; Shahwani, Hamayoun; Attique Shah, Syed; Gyu Yang, Jun
Summary: This study presents the electromagnetic (EM) field uniformity analysis of the Korean National Radio Research Agency (RRA) reverberation chamber (RC). The analysis is performed using the normative procedure of International Electrotechnical Commission (IEC) 61000‐4‐21 for the estimation of the lowest usable frequency (LUF) of the RRA RC based on the field uniformity characterization. A full‐wave EM model of the RRA RC is designed using the method‐of‐moments (MOM) technique. The triaxial electric fields at the eight corners of the defined working volume are measured using electric field probes for the complete revolution of the mechanical stirrer. The experimental data are obtained for the frequency range of 80–1, 000 MHz through the designed data acquisition software. The post‐processing of the experimental and simulation data in terms of calculation of standard deviation of recorded E‐field data, and its comparison with the defined standard deviation limit in IEC 61000‐4‐21 standard is performed to obtain the LUF of the RRA RC. A good degree of agreement was observed between the simulated and measured results of the RC field uniformity. Abstract : This study presents the numerical and measurement‐based electromagnetic (EM) field uniformity analysis of the Korean National Radio Research Agency (RRA) reverberation chamber (RC) using IEC 61000‐4‐21 for the determination of LUF.